Uzbekistan Insurance Market: Targeted Development Indicators and General Insurance Market Analysis - SH.T.Islamov (Zien Journals, 2022)
As is generally known, insurance relations and insurance services occupy the special place in development of world economy. The incremental analysis of indexes of having a special purpose insurance market development is therefore important. In the article the indexes of having a special purpose insurance market of Uzbekistan development are analyzed in the future their classification. In addition, correlation of having a special purpose index is studied for passing ahead insurance market of Uzbekistan development, and on the basis of this cross-correlation analysis drawn conclusion, the closeness of correlation is certain.
Keywords: insurance companies; insurance services; insurance market integration; level of development